A case of neuronal intranuclear inclusion disease with recurrent vomiting and without apparent DWI abnormality for the first seven years - Shun Okamura (Heliyon, 2020)
Neuronal intranuclear inclusion disease (NIID) is a rare, neurodegenerative disorder characterized by the presence of eosinophilic hyaline intranuclear inclusions, which are ubiquitin-positive and p62-positive, in neuronal and somatic cells; this can be observed on skin biopsy. Although patients with NIID present with a variety of symptoms that often make the diagnosis difficult, characteristic high-signal intensity of the corticomedullary junction on diffusion-weighted imaging (DWI) often provides a clue to the diagnosis of NIID. We present a case of NIID in a 57-year-old woman who only had recurrent vomiting for four years, which is uncommon as the presenting symptom; moreover, DWI showed no apparent abnormality until a slightly abnormal intensity lesion appeared at the right frontal corticomedullary junction seven years after the first episode of recurrent vomiting. Skin biopsies revealed multiple p62-positive nuclear inclusions, and genetic test showed GGC repeat expansion in NOTCH2NLC; this may form the genetic basis for NIID. Retrospectively, we found that abnormal cerebellar signals besides the vermis in the fluid attenuation inversion recovery (FLAIR) images were detected early-on in the disease. Periodic vomiting may be the only symptom of NIID in the early stages of the disease, and cerebellar abnormalities in FLAIR may serve as an important finding in the diagnosis of NIID, even in the absence of characteristic clinical symptoms or abnormal DWI signals at the cerebral corticomedullary junction.